Assessment of Integrated Marketing Communication (IMC) and Customer Patronage of Selected Nigerian Noodles - Babaiya, Yuhannasu Muhammad; Akase, T. M.; Kente, J. S. (EDUMALSYS Journal of Research in Education Management, 2025)
Amid intensifying competition in Nigeria’s fast-moving consumer goods sector, this study assesses how Integrated Marketing Communication (IMC) strategies influence customer patronage of Indomie and Dangote noodles in Lafia Metropolis. The objective is to determine the most prominent IMC tools driving patronage and to compare stakeholder perceptions of IMC effectiveness. Employing a survey research design, the study analyzes audience responses to the IMC activities of selected noodle brands. Key findings indicate that mass media advertising is the foremost IMC strategy promoting patronage, followed by souvenir distribution. Results further show that celebrity endorsement most strongly differentiates perceptions of IMC effectiveness across stakeholders—staff of noodle-producing companies, customers, and marketing communications organizations—followed by product quality. Overall, the IMC mix effectively shapes audience perceptions and converts prospects into regular consumers. The study concludes that IMC plays an indispensable role in promoting patronage of Indomie and Dangote noodles in the study context. The contribution lies in clarifying the relative salience of IMC instruments in a local market and highlighting practical implications: firms should review stringent in-house media policies to enhance agency collaboration, manage prime-time slots transparently (e.g., first-come, first-served) to curb favoritism and unhealthy competition, and avoid deceptive messaging, particularly given its potential impact on younger audiences.